CRISPR Detection and Research on Screening Mutant Gene TTN of Moyamoya Disease Family Based on Whole Exome Sequencing - Xiao, Yilei; Liu, Weidong; Hao, Jiheng; Jiang, Qunlong; Wang, Xingbang; Yu, Donghu; Zhang, Liyong; Dong, Zhaogang; Wang, Jiyue (Frontiers in Molecular Biosciences, 2022)
Moyamoya disease (MMD) has a high incidence in Asian populations and demonstrates some degree of familial clustering. Whole-exome sequencing (WES) is useful in establishing key related genes in familial genetic diseases but is time-consuming and costly. Therefore, exploring a new method will be more effective for the diagnosis of MMD. We identified familial cohorts showing MMD susceptibility and performed WES on 11 affected individuals to identify susceptibility loci, which identified point mutation sites in the titin (TTN) gene (rs771533925, rs559712998 and rs72677250), although mutations in other known MMD susceptibility genes (RNF213, MMP3) were not detected. Moreover, TTN mutations were not found in a cohort of 50 sporadic MMD cases. We also analyzed mutation frequencies and used bioinformatic predictions to reveal mutation harmfulness, functions and probabilities of disease correlation, the results showed that rs771533925 and rs72677250 were likely harmful mutations with GO analyses indicating the involvement of TTN in a variety of biological processes related to MMD etiology. CRISPR-Cas12a assays designed to detect TTN mutations provided results consistent with WES analysis, which was further confirmed by Sanger sequencing. This study recognized TTN as a new familial gene marker for moyamoya disease and moreover, demonstrated that CRISPR-Cas12a has the advantages of rapid detection, low cost and simple operation, and has broad prospects in the practical application of rapid detection of MMD mutation sites.